MATHEMATICAL MODELING OF GAS DYNAMICS OF POWDER STREAM IN IMPLEMENTATION OF RAPID PROTOTYPING TECHNOLOGY - Кондрашев, Павло Васильович (Eastern-European Journal of Enterprise Technologies, 2013)
In the modern world of rapid development of scientific and innovative technologies it is impossible to imagine any industry without using laser technology. Such a universal tool as laser can be used by many modern technologies, one of which is Rapid Prototyping technology, widely used in highly developed countries all over the world for immediate production (e.g. production of dies, press-molds, etc.). Despite the smashing success of laser technique and technology, developers face the issues of increasing the productivity and quality of forming the products from powder materials. The author’s method, aimed at improving the quality parameters of products obtained due to the implementation of Rapid Prototyping technology, is presented in the paper. The method is based on numerical simulation of gas-dynamic processes taking place in a gas-powder stream. This approach is implemented using the Ansys CFX software package, which is an indispensable tool in modern engineering and allows solving a great variety of issues in the field of fluid dynamics. The method allows developing the means of powder composition delivery to the laser radiation area with optimal aerodynamic parameters. Thus, the research results, given in the paper, are of scientific and practical interest. The author showed the opportunity of using the method of numerical simulation of the gas-powder stream behavior for designing the coaxial nozzles that allows increasing the quality parameters of products obtained due to the Rapid Prototyping technology.